Call admission control for QoS provisioning in 4G wireless networks issues and approaches. - Niyato, D.
This article presents a survey on the issues and the approaches related to designing call admission control schemes for fourth-generation wireless systems. We review the state of the art of CAC algorithms used in the traditional wireless networks. The major challenges in designing the CAC schemes for 4G wireless networks are identified. These challenges are mainly due to heterogeneous wireless access environments, provisioning of quality of service to multiple types of applications with different requirements, provisioning for adaptive bandwidth allocation, consideration of both call-level and packet-level performance measures, and consideration of QoS at both the air interface and the wired Internet. To this end, architecture of a two-tier CAC scheme for a differentiated services cellular wireless network is presented. The proposed CAC architecture is based on the call-level and packet-level QoS considerations at both the wireless and wired parts of the network. A performance analysis model for an example CAC scheme based on this architecture is outlined, and typical numerical results are presented.
Keywords: 4G wireless networks; CAC; QoS provisioning; Adaptive bandwidth allocation; Call admission control; Call level performance measures; Fourth generation wireless systems; Packet level performance measures; Performance analysis models; Quality of service